An approach to local immunotoxicity induced by adjuvanted vaccines - Batista-Duharte, Alexander; Portuondo, Deivys [UNESP]; Carlos, Iracilda Zeppone [UNESP]; Pérez, Oliver (Elsevier, 2013)
The occurrence of injection site reactions following immunization is the most frequently reported toxicity manifestation of vaccines; however, the different types of local reactions and the different mechanisms involved are still unclear. Here, the current advances in adjuvants and the role that adjuvants play in local reactions are reviewed. The role of adjuvants in the formation of the loco-regional complex (LRC), which consists of the injection site, draining lymphatic vessels and regional lymph nodes, is also discussed. Finally, strategies and recommendations for the rational design of adjuvanted vaccines are discussed, with a particular interest in the reduction of local inflammation. © 2013 Elsevier B.V.
Keywords: Action mechanism; Adjuvant; Immunotoxicity; Local reaction; Vaccine; BCG vaccine; poliomyelitis vaccine; vaccine; adaptive immunity; antigen presenting cell; Arthus phenomenon; BCG vaccination; carcinogenesis; delayed hypersensitivity; drug induced disease; granuloma; human; immunization; immunotoxicity; injection site nodule; innate immunity; lymphadenitis; lymphatic drainage; lymphoid hyperplasia; Persian Gulf syndrome; priority journal; pseudolymphoma; subcutaneous nodule; tuberculosis; urticaria